Suture Related Iatrogenic Bladder Stone - Hikmet Köseoğlu; Ramazan Yavuz Akman (Journal of Urological Surgery)
Iatrogenic suture materials within bladder cavity related to previous bladder surgeries or others with proximity to bladder may cause stone formation around themselves. This phenomenon has been well characterized with experimental animal studies. Though care related to choice of suture and technique of suturing is taken for, still such cases are reported after both urological and non-urological surgeries. In this report, such a case that had been operated for incontinence previously is presented for stone formation around the suture material within bladder cavity together with radiological examinations and endoscopical visualizations.